Evaluación de una tecnología para el aprovechamiento sostenible de los residuos sólidos orgánicos para la obtención de biogás en la finca “El Rubí” en Silvania Cundinamarca (2020)
The following work is based on the evaluation of the optimal technology for the sustainable use of organic solid waste obtained on the family economy farm "El Rubí" by waste from the processes of coffee, milking, trees and others, achieving the production of biogas for some facilities of the farm. To begin this work, extensive research was carried out in the literature to find information about existing farm types, waste harvesting technologies, types of biodigesters and their respective characteristics. Then, research was carried out focused on the farm "El Rubí", where the characteristics of it, its waste and needs were identified, concluding a production of 8.5 m3 of organic waste obtained weekly.